Stabilization and reversal of child obesity in Andalusia using objective anthropometric measures by socioeconomic status - José-Juan S; I de Ruiter; J J Jiménez-Moleón; Ll García; Maria-Jose Sánchez (BMC, 2018)
Abstract Background Childhood obesity continues to be a significant public health issue worldwide. Recent national studies in Spain show a stable picture. However, prevalence and trends differ by socio-economic status, age, and region. We present the trend in childhood excess weight prevalence, aged 8-15 years, in Andalusia from 2011-2012 to 2015-2016 by socio-economic status. Methods Using the cross-sectional Andalusian Health Surveys, objective anthropometric measures were taken for a representative sample of 8-15 year olds in Andalusia in 2011-2012 and 2015-2016. Prevalence and changes in prevalence of excess weight (overweight plus obesity) were calculated, using both the WHO and IOTF criteria, overall and for sex, age and three different indicators of SES. Results Overall prevalence of excess weight decreased from 42.0% in 2011-2012 to 35.4% in 2015-2016. Overweight decreased from 28.2 to 24.2% and obesity from 13.8 to 11.2%. In 2011-2012 the prevalence of excess weight in boys was 46.0%and 37.9% in girls; in 2015-2016 the difference became significant with 41% of boys with excess weight compared with 30% in girls. Conclusions Childhood excess weight prevalence in Andalusia has decreased slightly between 2011-2012 and 2015-2016. Notably, a decrease in obesity prevalence in girls aged 8-15 years was recorded. In 2011-2012 a social gradient for excess weight prevalence across three SES indicators was observed: in 2015-2016 this gradient disappeared. Nonetheless, prevalence remains too high.